Icchokas Meras’ ‘Lygiosios trunka akimirką’ (Stalemate) in the Unequal Battle Against the Censors. The editorial office of Дружба народов. A transcript of a scrutiny of comr. Meras’ manuscript. July 8, 1963. - Mačianskaitė, Loreta (Colloquia, 2024)
-
Keywords: -